2019
DOI: 10.3892/etm.2019.7289
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of propofol in preventing emergence agitation after sevoflurane anesthesia for children

Abstract: Application of propofol in preventing emergence agitation after sevoflurane anesthesia in children was evaluated. Clinical data of 200 children who received sevoflurane anesthesia in Children's Hospital of Xuzhou Medical University were retrospectively analyzed. Among them, 120 patients who received inhaled sevoflurane for pediatric anesthesia and intravenous infusion of propofol (2 mg/kg) were included in observation group. The remaining 80 cases who were directly anesthetized by sevoflurane alone were the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…These findings have been confirmed in a recent study where the infusion of 3 mg/kg propofol over three minutes also was found to reduce ED frequency [24]. Furthermore, a study with an IV propofol administration of 2 mg/kg near the end of sevoflurane anesthesia also reported a significant decrease in the incidence of ED, measured by PAED scale (5.66 ± 1.74 vs 9.87 ± 3.15; P < 0.01) [25]. Fewer adverse events of the gastrointestinal tract and respiratory response (5% vs 13.75%; P = 0.03) were also found.…”
Section: Propofolsupporting
confidence: 69%
“…These findings have been confirmed in a recent study where the infusion of 3 mg/kg propofol over three minutes also was found to reduce ED frequency [24]. Furthermore, a study with an IV propofol administration of 2 mg/kg near the end of sevoflurane anesthesia also reported a significant decrease in the incidence of ED, measured by PAED scale (5.66 ± 1.74 vs 9.87 ± 3.15; P < 0.01) [25]. Fewer adverse events of the gastrointestinal tract and respiratory response (5% vs 13.75%; P = 0.03) were also found.…”
Section: Propofolsupporting
confidence: 69%
“…It is characterized by low aroma irritation, little effect on heart rate and hemodynamics, rapid anesthesia induction, and outstanding sedation and muscle relaxation effects [ 12 , 13 ]. However, it can lead to neurological disorder in the postoperative recovery period, such as vertigo, headache, agitation, nausea and vomiting, and uneven hemodynamic indicators, affecting the physical and mental health of the patient [ 14 , 15 ]. Therefore, it is necessary to use drugs during surgery to prevent adverse reactions caused by sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the children undergoing inhalation anesthesia through sevoflurane, isoflurane, or desflurane may suffer from a high incidence of post-anesthesia EA or ED (87,88). Various medications have been used to prevent EA or ED in pediatric patients, like benzodiazepines, opioids, propofol, ketamine, clonidine, dexmedetomidine, and so on (11,(89)(90)(91)(92)(93).…”
Section: Discussionmentioning
confidence: 99%